Opportunistic screening using point-of-care testing leads to successful linkage to care of HBV-infected migrant populations in a low endemic country - Erwin Ho; Axelle Vanderlinden; Liesbeth Govaerts; Bo De Fooz; Pierre Van Damme; Peter Michielsen; Thomas Vanwolleghem (Elsevier, 2024)
Background and aims: In low endemic countries, screening for hepatitis B surface antigen (HBsAg) in migrants is cost-effective in reducing the disease burden of hepatitis B virus (HBV) infections, but linkage to care (LTC) remains a challenge. This study aims to guide future screening initiatives, with 3 objectives: 1. to compare LTC between different ethnic groups screened for HBsAg with point-of-care testing (POCT) in an outreach setting; 2. to estimate the proportion of HBsAg seropositivity for ethnic minorities; and 3. to investigate the association between seropositivity and HBV risk factors. Methods: Opportunistic outreach screenings using finger prick HBsAg tests were performed at civic integration programmes between 11/2017 and 09/2022. If an individual tested positive, an appointment was given immediately at the outpatient hepatology clinic for follow-up and confirmation of HBsAg positivity in blood. Dedicated personnel contacted these individuals to motivate them for further LTC, which was defined as being assessed by a hepatologist, a blood test and an abdominal ultrasound. Results: A total of 677 people from different ethnicities (Asian, Middle Eastern and African) were serologically screened using POCT. The observed positivity for HBsAg was 3.4 % (95% CI 2.17-5.05, 23/677). Apart from ethnicity and male sex, none of the surveyed HBV risk factors were associated with HBsAg seropositivity. All HBsAg positive individuals were linked to care and assessed by a hepatologist, despite the COVID-19 pandemic increase in time to follow-up of 82 days (95% CI 51-112 days) vs. 24 days (95% CI 5-43 days, p = 0.008)).Among HBV-infected patients, 31.8% (7/22), 100 % (22/22) and 26.1% (6/23) met the criteria for treatment indication, intrafamilial transmission risk and need for hepatocellular carcinoma surveillance, respectively. Conclusion: The proportion of HBsAg seropositivity in ethnic minorities was 3.4%. POCT and commitment of dedicated personnel can overcome previously identified barriers resulting in a 100% LTC.